2021
DOI: 10.1016/j.msard.2020.102604
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features and Prognosis of Anti-NMDAR Encephalitis Depends on Blood Brain Barrier Integrity

Abstract: Background: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune nervous system disease that has become increasingly recognized. This retrospective study is aimed to analyze the relations between clinical manifestations and blood brain barrier (BBB) integrity in anti-NMDAR encephalitis patients. Methods: Anti-NMDAR encephalitis patients were admitted to the First Affiliated Hospital of Guangxi Medical University from April 2014 to April 2020. Patients were grouped by the normal BBB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
2
31
1
2
Order By: Relevance
“…Immunological and pathological shreds of evidence have proven that NMDAR autoantibodies were synthesized systemically and within the central nervous system (CNS) by antibody-producing cells that can cross the blood-brain barrier (BBB) [27,[61][62][63][64][65]. The central memory cells, plasma cells, and autoantibodies (specific IgG antibodies) circulated through the blood and lymphatic systems, then reached the CNS and eventually crossed the BBB.…”
Section: The Association With Teratoma-related Anti-nmdar Encephalitis and Blood-brain Barrier Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological and pathological shreds of evidence have proven that NMDAR autoantibodies were synthesized systemically and within the central nervous system (CNS) by antibody-producing cells that can cross the blood-brain barrier (BBB) [27,[61][62][63][64][65]. The central memory cells, plasma cells, and autoantibodies (specific IgG antibodies) circulated through the blood and lymphatic systems, then reached the CNS and eventually crossed the BBB.…”
Section: The Association With Teratoma-related Anti-nmdar Encephalitis and Blood-brain Barrier Integritymentioning
confidence: 99%
“…Nevertheless, the mechanism by which the autoantibodies cross the BBB is not yet fully understood [56]. One potential explanation was that the immune and inflammatory response in patients with ovarian teratoma and anti-NMDAR encephalitis might damage the integrity of capillaries and lead to the dysfunction of BBB [65]. Notably, Jiang et al showed increasing levels of TNF-α, IL-10, and GM-CSF in patients with teratoma-related anti-NMDAR encephalitis compared to the control group, indicating the involvement of the inflammation process in the pathogenesis [52].…”
Section: The Association With Teratoma-related Anti-nmdar Encephalitis and Blood-brain Barrier Integritymentioning
confidence: 99%
“…25 Moreover, rates of seropositivity in healthy individuals are not significantly different from those in affected individuals; blood brain barrier permeability and activation of intrathecal antibody production are thought to be the major determining factors in whether disease develops. [25][26][27][28] Therefore, in practice, a positive serum resulteven in a patient with psychosisdoes not automatically equate to a diagnosis of anti-NMDAR encephalitis. 29 However, it does mean further investigation is warrantedat a minimum with CSF analysis, EEG and MRI of the headand expert neurology evaluation should be sought.…”
Section: Nmdar Antibody Testingmentioning
confidence: 99%
“…PSH was diagnosed according to the PSH-Assessment Measure (PSH-AM) proposed by Baguley et al based on the Clinical Feature Scale (CFS) and Diagnosis Likelihood Tool (DLT). The clinical features were classi ed as mild (1-6), moderate (7)(8)(9)(10)(11)(12), severe (>12) group according to CFS. Both scores were added to determine the likelihood of PSH as unlikely (< 8), possible (8-16) and probable (≥17) [15].…”
Section: Patient Eligibilitymentioning
confidence: 99%
“…Approximately 10-50% of the anti-NMDAR encephalitis patients have autonomic dysfunction [2,9], including tachycardia/bradycardia, hypertension/hypotension, gastrointestinal dysfunction, urinary dysfunction, abnormal pupil movement etc., which increase patient morbidity and mortality, complicate intensive care and can lead to hemodynamic shock [10]. However, little is known regarding the correlation between autonomic instability and the prognosis of autoimmune encephalitis, and the conclusions are ambiguous [4,11].…”
Section: Introductionmentioning
confidence: 99%